Perioperative impact of sleep apnea in a high-volume specialty practice with a strong focus on regional anesthesia: a database analysis. Issue 3 (March 2019) - Pichler, Lukas; Weinstein, Sarah M; Cozowicz, Crispiana; Poeran, Jashvant; Liu, Jiabin; Poultsides, Lazaros A; Saleh, Jawad N; Memtsoudis, Stavros G
Abstract : Background and objectives: Obstructive sleep apnea (OSA) is a risk factor for adverse postoperative outcome and perioperative professional societies recommend the use of regional anesthesia to minimize perioperative detriment. We studied the impact of OSA on postoperative complications in a high-volume orthopedic surgery practice, with a strong focus on regional anesthesia. Methods: After Institutional Review Board approval, 41 766 cases of primary total hip and knee arthroplasties (THAs/TKAs) from 2005 to 2014 were extracted from institutional data of the Hospital for Special Surgery (approximately 5000 THAs and 5000 TKAs annually, of which around 90% under neuraxial anesthesia). The main effect was OSA (identified by the International Classification of Diseases, ninth revision codes); outcomes of interest were cardiac, pulmonary, gastrointestinal, renal/genitourinary, thromboembolic complications, delirium, and prolonged length of stay (LOS). Multivariable logistic regression models provided ORs, corresponding 95% CIs, and p values. Results: Overall, OSA was seen in 6.3% (n=1332) of patients with THA and 9.1% (n=1896) of patients with TKA. After adjustment for relevant covariates, OSA was significantly associated with 87% (OR 1.87, 95% CI 1.51 to 2.30), 52% (OR 1.52, 95% CI 1.13 to 2.04), and 44% (OR 1.44, 95% CI 1.31 to 1.57) increased odds for pulmonary gastrointestinal complications, and prolonged LOS, respectively. The odds for other outcomes remained unaltered by OSA diagnosis. Conclusion: We showed that, even in a setting with almost universal regional anesthesia use, OSA was associated with increased odds for prolonged LOS, and pulmonary and gastrointestinal complications. This puts forward the question of how effective regional anesthesia is in mitigating postoperative complications in patients with OSA.